PENGARUH PENGGUNAAN ALAT PERAGA TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Mawi Hendarto; Ayu Tasya (Hipotenusa Journal of Research Mathematics Education (HJRME), 2018)
In the learning process, not every student succeeds through the learning process carried out, in other words, not every student can achieve the learning objectives as expected, there are still many students who are less successful. In the process and learning outcomes can be successful or not influenced by many factors, including intelligence, readiness to learn, interest, motivation, teacher ability, maturity, family, school and community. Teaching aids in the teaching and learning process can generate desire and interest, generate motivation, stimulate learning activities and even psychological influence on students. The author in this study uses quantitative descriptive methods, data analysis using statistical formulas. The population in this study were all students of class X SMA Perintis 1 Bandar Lampung which consisted of 9 classes with a total of 398 students, while the sample was taken 2 classes, namely X.2 as the experimental class and X.3 as the control class. . Test the hypothesis by using the statistical formula t-test. From the results of hypothesis testing using the statistical formula t-test, the value of t = 4.62 is obtained. From the t distribution table at the 5% significant level, it is known that t = t = 1.993 and t = 1.67, while at the 1% significant level it is known that t = t = 2.65 and t = 2.39, this means t > t. So with this it can be said that there is an effect of the use of teaching aids on the mathematics learning outcomes of X SMA Perintis 1 Bandar Lampung students and the average mathematics learning outcomes of students who use teaching aids are higher than the average learning outcomes of students who do not use teaching aids. Thus, it can be said that the use of teaching aids is positive or can improve mathematics learning outcomes.